Currency boards and external shocks : how much pain, how much gain? - Perry, Guillermo E.; Calvo, Guillermo A. (Washington, D.C. : World Bank, 1997)
Currency Boards also impose fiscal discipline because expenditures cannot be financed by printing money.
"Proceedings"--Cover.
Includes bibliographical references.
aia 28/09/2016
Loans
Keywords: Currency boards-- Congresses; Business and Economics-Money and Monetary Policy